Effect of P-glycoprotein regulation on cadmium exhaustion from Crassostrea gigas. (April 2019) - Yang, Chao; Liu, Qingkang; Li, Guangzhen; Meng, Xianghong; Liu, Bingjie
Abstract: P-glycoprotein (P-gp) is a molecular pump, responsible for extruding xenobiotics. The aim of the study was to demonstrate the role of P-glycoprotein (P-gp) in cadmium (Cd) exhaustion. The activity of P-gp was regulated in Crassostrea gigas, which was previously exposed to Cd by using rifampicin (inducer) and verapamil (inhibitor), respectively. Comparing with Crassostrea gigas depurated in natural seawater, Cd content increased significantly from 14.28 mg/kg dw to 17.49 mg/kg dw accompanied by a changed metallothionein level from 9.84 μg/g fw to 10.67 μg/g fw after 25 μg/L verapamil treatment, while Cd content after 25 μg/L rifampicin treatment reduced to 12.21 mg/kg dw. Moreover, after treatment with rifampicin and verapamil, beneficial metal elements, fats, and proteins were maintained, and the tissue-dependent difference was found in the variation of antioxidant defenses and oxidative damage in Crassostrea gigas . In brief, the study provided new evidence on possibility of Cd removal by inducing P-glycoprotein. Highlights: P-glycoprotein (P-gp) was effective for Cd excretion from Crassostrea gigas . Beneficial metal elements, fats, and proteins in Crassostrea gigas were not reduced after inducing P-gp with rifampicin. Variation of antioxidant defenses and oxidative damage were tissue-dependent when it was treated by rifampicin and verapamil.